(untitled) (The Journal of Plant Protection Sciences, 2022)
A field experiment was carried out at ‘C’ Block Farm, Bidhan Chandra Krishi Viswavidyalaya, Kalyani, Nadia West Bengal in two consecutive years (2009-10 and 2010-11) to study the effect of different weed management measures (e.g. hand weeding, herbicides, mulching etc.) on the yield of crops in sequence and cost effectiveness of different weed control measures. Rice exhibited the maximum yield when treated with two hand weedings, but it may be profitably replaced by the application of herbicides. From the point of eco-safety measures and economy, combination of hand weeding and mulching can be judiciously recommended in potato and groundnut.